STUDYING ENGLISH LITERATURE IN INDONESIA: CHALLENGES AND OPPORTUNITIES - Novita Dewi (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2018)
This article examines the challenges and opportunities for students of English Literature in Indonesia amidst forces of globalization and technological advancements in most aspects of life. Demographic transition of users and providers of the English language has brought about such challenges as observable lack of maturity in English scholarship and automation’s impact on education today. It can be argued that such challenges can be seen as opportunities by a creative rather than product-oriented curriculum. Given that studying literature is not only to train cognitive skills of interpreting texts, English Literature teaching in Indonesia should also impart values so as to inspire learners into becoming autonomous, self-fulfilled and emancipated global citizen. Opportunities are open if studying English Literature can include humanistic-contextual topics, discerning use of technology and transformative research method.